MEMBANGUN VISUALISASI BELAJAR SISWA SMA MATERI DIMENSI TIGA DENGAN MENGGUNAKAN APLIKASI GEOGEBRA (Universitas Wijayakusuma Purwokerto, 2024)
This Community Service activity aims to increase the knowledge of high school students, especially class X, about drawing three-dimensional shapes using the Geogebra application. Three-dimensional material is explained when occupying class XII, but the material described about three dimensions is more in-depth with an analysis related to problems or calculations about three dimensions so that students must already understand the shape of the three dimensions. This service activity is a collaboration of Medan Area University lecturers from various clusters of science and faculties, namely the faculties of engineering, psychology, economics and business. The implementation of this service activity was carried out on class X students attended by 26 students at Harapan Medan High School. Based on the results of the implementation of this service activity, it can be seen that changes occurred after the students used the geogebra application in drawing various three-dimensional shapes. 77% experienced changes for students in understanding the use of geogebra applications, 61.6% experienced changes for students in understanding three-dimensional drawing using geogebra applications and 38.51% experienced changes for students in knowing the elements of three-dimensional shapes. Thus, it can be concluded that the use of geogebra in learning three-dimensional mathematics can improve students' understanding and develop their visualization skills. Outputs in this PkM activity are in the form of videos, IPR and journal publications.